CNTFET SPICE model: design of a carbon nanotube field effect transistor - Farhana, Soheli; Alam, A. H. M. Zahirul; Khan, Sheroz; Motakabber, S.M.A. (2014)
In this paper, we elucidate the development of SPICE model of Carbon Nanotube Field Effect Transistor (CNTFET) and analyze the performance of the proposed model. A set of key parameter can be obtained from this model analysis such as drain current variation as a function of the conductance and drain-source voltage. Furthermore, a SPICE small signal model nanotube transistor is developed. It is used for studying the performance of current gain as well as design of nanotube transistor circuits and phase angle with cut-off frequency. CNT diameter is responsible for the better performance of CNTFET. Therefore an optimum diameter of CNT is imposed here to develop CNTFET.